The Functions and Meanings of Dalihan Na Tolu for the Toba Batak Tribe: Oral Tradition Study - siahaan, jamorlan; barus, asni (Center of Language and Cultural Studies, 2023)
Oral traditions, oral culture and oral customs are messages or testimonies that are passed down from generation to the next generation. The message or testimony is deliverd by words, speeches, songs, and can be in the form of rhymes, folklore, advice, ballads, or songs. Dalihan na tolu means three pillars of the furnace. Dalihan is made by stone that is arranged neatly so the shape becomes elongated round and has a blunt end so that it can be used as a place for cauldrons and pots so that they doesn’t shake. The formulation of the problem in this research are 1) What is the function of dalihan na tolu, 2) What is the meaning of dalihan na tolu, 3) What is the message of dalihan na tolu. The aims and benefit of this research are to describe the meaning and the function as well as the message that be delivered to the community, while the benefit is to develop the knowledge and support the institution/management. The theory used is the theory of Dj. Rajamarpodang G. (1995). The basic method is the method that used in terms of the data collection process, to the analysis stage by applying to the subject matter. This research method used a descriptive method, namely research that seeks to describe a current problem that solving based on data as well as presenting data and interpreting data (Narbuko, 1994:4). The discussion in this dalihan na tolu research is to explain the hulahula (uncle), boru (female) group and the dongan sauntunga (semarga friends) group in the event of joy and sorrow in terms of meaning, message and function be delivered orally.